Zakat Fund Management System at Masjid Akbar Kedepatian Semerap - Saputra, Aldi; Fitri, Lucky Enggrani; Ridhwan, Ridhwan; Suhaimi, Amanda (Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2023)
This study aims to determine the management of zakat funds, opportunities and obstacles in the management of zakat funds and strategies for managing zakat funds at the Kedepatian Semerap Akbar Mosque. The type of data used in this research is primary data by conducting interviews with several sources such as Muzakki, Mustahik, Village Head, Amil, Traditional Leaders, KUA. The results of this study indicate that the zakat fund management system at the Akbar Kedepatian Semerap mosque uses manual recording, and has its own system that is regulated directly by custom, before the distribution of zakat funds Amil first gives coupons to Mustahik's house which is given 2-3 days before Eid al-Fitr.